(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This article discusses the issues of improving the methodology of teaching engineering graphics through Building Information Modeling (BIM)-based software technologies. Today, the rapid development of digital technologies requires the integration of innovative software into the educational process. In particular, the use of Autodesk Revit and other BIM-oriented programs in engineering graphics education helps students develop spatial imagination, graphic competence, and practical design skills. The article analyzes the didactic possibilities of BIM technologies, the advantages of parametric modeling, and the effectiveness of digital teaching methods. In addition, experimental results and methodological recommendations for organizing practical lessons based on BIM technologies are presented.